Kualitas Pelayanan “Vending Machine” dengan Metode Importance and Performance Analysis pada PT KAI Commuterline Jabodetabek - Nafisah Yuliani; Diana Novita (STIE Indonesia Banking School, 2018)
The exists of Vending Machine which even socialite in purpose yet, cause many difficulties to passengers of KRL Commuter Line. The purpose of this research is to get to know how the quality services of Vending Machine based on Importance and Performance Analysis (IPA) method. The research method that use to write this research is a descriptive method. The method of gathering and collecting the data for this research are using the survei method and Purposive Sampling method. The research held in Jakarta with 121 people as a sample of research. The research variable that uses in this is a qualiyy service such as Tangibility, Realibility, Responsiveness, Assurance and Empty. This questionnaire organize based on a likert scale with the scale is 1 to 5. The analysis technique which is done is data measurements, questionnaires validity tests, questionnaires reliabilities tests, IPA Analysis. The result of GAP score from those five is gain with the average of customers satisfaction levels which are negative, it means that customers are not satisfied with the Vending Machine services. So, it still necessary to open the tickets sales through a locker while keeping on socialite about how to use Vending Machine which are hope, in the future will make a Commuter Line ticket sales become easier. The main points that should be fixed in order to increase the quality services of Vending Machine are room cleanness, the shortest line of services, the fastest and goodness employe eon giving information, responsiveness when some mistakes happened.